Respuesta :

The exponential equation is [tex]y=-6(3)^{x}[/tex]

Step-by-step explanation:

The form of the exponential function is [tex]y=a(b)^{x}[/tex] , where

  • a is the value of y at x = 0
  • b is the exponential factor

∵ The exponential function passes through point (-1 , -2)

x = -1 and y = -2

- Substitute them in the form of the equation

∵ [tex]y=a(b)^{x}[/tex]

∴ [tex]-2=a(b)^{-1}[/tex]

- Remember [tex]b^{-1}=\frac{1}{b}[/tex]

∴ [tex]-2=a(\frac{1}{b})[/tex]

- Multiply both sides by b

∴ -2 b = a

- Switch the two sides

a = -2 b

∵ The exponential function passes through point (3 , -162)

x = 3 and y = -162

- Substitute them in the form of the equation

∵ [tex]-162=a(b)^{3}[/tex]

- Substitute a by -2 b

∴ [tex]-162=-2b(b)^{3}[/tex]

- Divide both sides by -2

∴ [tex]81=b(b)^{3}[/tex]

- Remember [tex]b.b^{x}=b^{x+1}[/tex] , when we multiply same

   bases we add their exponents

∵ [tex]b.b^{3}=b^{3+1}[/tex]

∴ [tex]b.b^{3}=b^{4}[/tex]

- Substitute it in the equation

∴ [tex]81=(b)^{4}[/tex]

- Take [tex]\sqrt[4]{}[/tex] for both sides

b = 3

- Substitute the value of b in a = -2 b to find a

∵ a = -2 b

∴ a = -2(3)

a = -6

- Substitute the values of a and b in the form of the exponential

   equations above

∴ [tex]y=-6(3)^{x}[/tex]

The exponential equation is [tex]y=-6(3)^{x}[/tex]

Learn more:

You can learn more about the logarithmic function in brainly.com/question/11921476

#LearnwithBrainly

ACCESS MORE